Elementary School Students' Perceptions of the New Science and Technology Curriculum by Gender - Gomleksiz, Mehmet Nuri (Int Forum Educational Technology & Soc, Natl Taiwan Normal Univ, 2012)
The purpose of this study is to explore students' perceptions of science and technology classes by gender in a Turkish elementary school context. Data for the study were collected through a 20-item, five-point Likert scale from a total of 1558 sixth-grade students at 20 different elementary schools in Turkey. The independent groups' t-test and Mann-Whitney U test were used to analyze the data. Statistically significant differences were observed in the gender of the students. Male students considered learning science and technology more necessary and important than female students did. They also found learning environment and teaching strategies more sufficient and effective than females did. Findings revealed that male students were not satisfied with what the teachers practised in science classrooms. Additionally, some useful implications are discussed based on the research findings to construct and conduct science and technology classes effectively.
Keywords: Elementary schools; gender; science teaching; science curriculum; Science education; technology education